Pro-inflammatory and anti-inflammatory cytokine expression in post-treatment apical periodontitis - Nilton Dessaune Neto; Mariana Teixeira Maneschy Porpino; Henrique dos Santos Antunes; Renata Costa Val Rodrigues; Alejandro Ron Perez; Fábio Ramôa Pires; José Freitas Siqueira Jr; Luciana Armada (University of São Paulo, 2018)
Abstract Objective: This study evaluated the expression of pro-inflammatory (IL-1β, IL-6, IFN-γ and TNF-α) and anti-inflammatory (IL-4 and TGF-β) cytokines in apical periodontitis lesions. Correlations between these cytokines and clinical and cone-beam computed tomographic (CBCT) data were also assessed. Material and Methods: Apical periodontitis lesions' data were obtained from 27 patients subjected to periradicular surgery. Specimens were processed for histopathologic and immunohistochemical analysis. Sections were evaluated according to the amount of positive staining for each antibody. Expression levels of the target mediators were compared with clinical and CBCT data. Results: Twenty lesions were diagnosed as granuloma and 7 as cyst. In granulomas, IL-4 expression was significantly higher than IL-6 (p=0.001) and TNF-α (p=0.001). There was a significant relationship between high levels of TNF-α and lesions <5 mm (p=0.017). In cysts, IL-6 expression was significant lower than IL-4 (p=0.001) and IFN-γ (p=0.004). There was a significant relationship between high levels of TGF-β and endodontic treatment performed ≤4 years before (p=0.045). In general, IL-4 was the most expressed mediator in both cysts and granulomas. Conclusions: There was a balance between the expression of pro-inflammatory and anti-inflammatory cytokines associated with the chronic periradicular inflammatory process. TNF-α and TGF-β were related to some clinical and CBCT data.